Chicken CircZNF609 encodes a protein induced by IRES-like region that inhibits the proliferation and promotes the differentiation of myoblasts - Lei Li; Zihao Zhang; Haidong Xu; Qiying Leng; Wenjin Shen; Shudai Lin; Lilong An; Li Zhang (Poultry Science)
Skeletal muscle is comprised of multinucleated myofibers that arise from myogenesis, a highly coordinated process encompassing the proliferation and differentiation of myoblasts. During this process, circular RNAs (circRNAs) are recognized as functional non-coding transcripts that play important roles in the regulation of skeletal myogenesis. Chicken ZNF609 (Zinc Finger Protein 609) is a member of the zinc finger proteins (ZNFs) family which serve as versatile regulators in cell proliferation, differentiation and metabolism. Analyze of circRNA sequencing data in chicken from our previous work revealed a circRNA originating from the ZNF609 gene, circZNF609. Here, we verified circZNF609 by sanger sequencing and RNase R treatment. And we found that chicken circZNF609 was upregulated in thigh muscles with the growth of chickens. Then we demonstrated that circZNF609 inhibited myoblast proliferation while promoting myogenic differentiation. Furthermore, we revealed a novel circ-ZNF609-encoded protein circZNF609-232aa that was responsible for the downregulation of myoblast proliferation and upregulation of differentiation. The translation of circ-ZNF609 was induced by its IRES-like regions. Our study not only presented a critical role of circ-ZNF609 in the regulation of myogenesis, but also identified a novel protein circZNF609-232aa which exerted its key effects, contributing to the understanding of complex skeletal muscle development.